The Role of Macroeconomic Indicators and Global Oil Prices in Influencing Indonesia’s Crude Oil Exports to South Korea - Auliani, Annisya; Purnomo, Didit (Journal of Enterprise and Development (JED), 2025)
Purpose: This study analyzes the impact of macroeconomic indicators and global oil prices on Indonesia's crude oil exports to South Korea, one of its strategic trading partners in the East Asia region.Method: A quantitative approach was employed using annual time series data comprising 24 observations from 2000 to 2023. Secondary data were obtained from official sources such as Statistics Indonesia (BPS), the World Bank, and Index Mundi. Data analysis was conducted using multiple linear regression with the Ordinary Least Squares (OLS) method.Results: The analysis indicates that South Korea’s inflation and GDP per capita growth positively affect Indonesia’s crude oil exports to the country. Conversely, the exchange rate and global oil prices negatively impact these exports.Practical Implications for Economic Growth and Development: These findings provide relevant policy insights for the Indonesian government in responding to global economic dynamics, including strategies for exchange rate stabilization, export market diversification, and strengthening economic diplomacy.Originality/Value: This study makes an original contribution by specifically examining the bilateral relationship of Indonesia’s crude oil exports to South Korea based on the dynamics of external variables. Its focus on a specific region and extended time coverage renders it a unique study that delivers tangible contributions rarely found in Indonesia’s international trade literature.